Medical Students, Mid-Level Providers, and Physician Attitudes Towards Yoga Practice During Pregnancy [25B]. (May 2017) - Bell, Sarah; Kobernik, Emily; Hammoud, Maya
Abstract : INTRODUCTION: Yoga is a widely practiced form of exercise in the United States. We examined the attitudes of medical students, mid-level providers, and physicians regarding the role of yoga in obstetric patient care. METHODS: A 21-question survey was distributed from June 2016 to July 2016 to all second, third, and fourth year medical students, mid-level providers, (nurse practitioners, physician assistants, midwives), and Obstetrics and Gynecology and Family Medicine physicians at the University of Michigan. Bivariate analyses comparing participants who indicated they would recommend yoga to obstetric patients and those who did not was performed. RESULTS: The response rate among physicians/mid-level providers was 39% (114/294) and 33% (190/581) among medical students. Among 299 surveys eligible for analysis, 75.9% had ever practiced yoga, and 40.3% were current practitioners of yoga. Nearly two-thirds (61.4%) of participants indicated they would recommend yoga to their obstetric patients. Recommending yoga to obstetric patients was significantly associated with agreeing yoga is "a good form of exercise" (82.6% versus 42.6%, p < .0001), "safe" (89.1% versus 48.9%, p < .0001), recommending it to non-pregnant patients (82.6% versus 27.7%, p < .0001), and gender (58.4% males versus 74.9% females, p < 0.003). Among males, lifting weights was negatively associated with recommending yoga (37.0% versus 61.7%, p=0.02), and among females, running was negatively associated with recommending yoga (56.2% versus 77.3%, p=0.004). CONCLUSION: The majority of medical students, mid-level providers, and physicians would recommend yoga to their obstetric patients. Further research is needed to identify the specific predictors of recommending yoga to obstetrics patients.